Middle Level Faculty and Change - Robin Dever (Current Issues in Middle Level Education, 2020)
There is no argument that the world of middle level education is constantly changing. Teacher education programs are always in flux adopting their programs to meet these needs. Faculty who teach within a middle level education teacher preparation program are at the front lines of preparing the next generation of middle school leaders. They are responsible for not only molding the next generation of middle level educators but also shaping the next generation of middle level education researchers and advocates. This requires constant changes to curriculum and organizational structures while finding new methods to meet state requirements. However, not all faculty is open to change and resist moving forward. Some are over-burdened by this charge and often resist changes that are being implemented to best prepare this next generation. Exploring the root cause of faculty resistance can help programs work with all faculty. This article will begin a conversation on how to lead faculty members through these journeys and empower them to continue to advocate for the field.